Lithiated Manganese-Based Materials for Lithium-Ion Capacitor: A Review - Ntuthuko W. Hlongwa; Naledi Raleie (Energies, 2022)
Lithium-ion capacitors (LICs) are a novel and promising form of energy storage device that combines the electrode materials of lithium-ion batteries with supercapacitors. They have the potential to deliver high energy density, power density, and long cycle life concurrently. Due to the good electrochemical performance of lithiated manganese-based materials in LICs, they have received extensive attention in recent years. The latest advancements in lithiated manganese-based materials as electrode materials in lithium-ion capacitors are presented here, including LiMnPO4, LiMn2O4, and Li2MnSiO4. These electrode materials have a lot of potential as high-performance energy storage materials. Apart from capacitive-type electrodes, lithiated manganese-based materials are also used in the creation of LIC battery-type electrodes. The LICs based on lithiated manganese-based electrode materials demonstrated energy density, power density, and cycle life, which are relatively comparable with various electrode material values reviewed in this paper. The electrochemical performance of lithiated manganese-based materials is attributed to the synergistic effect of the doping and the conductive carbon coating which provided new pathways for the movement of Li+ ions and electrons, thus facilitating charge transfer reactions. Although much effort has gone into synthesizing lithium-ion battery electrode materials and contracting LICs based on them because of their higher energy density, there is still work to be carried out. Additionally, the potential barriers and opportunities for LIC-based future research in energy applications are explored.